Schistosome egg antigen stimulates the secretion of miR-33-carrying extracellular vesicles from macrophages to promote hepatic stellate cell activation and liver fibrosis in schistosomiasis. - Xin Qi; Yanan Pu; Fanyan Chen; Liyang Dong; Yongbin Ma; Junling Wang; Guo Yin; Di Lu; Xiaojun Chen; Jifeng Zhu; Yalin Li; Sha Zhou; et al. (PLoS Neglected Tropical Diseases)
Schistosomiasis is a serious and neglected disease with a high prevalence in tropical and subtropical countries. The primary pathology of hepatic schistosomiasis caused by Schistosoma japonicum (S. japonicum) or Schistosoma mansoni (S. mansoni) infection is egg-induced granuloma and subsequent fibrosis in the liver. Activation of hepatic stellate cells (HSCs) is the central driver of liver fibrosis. Macrophages (Mφ), making up 30% of cells in hepatic granulomas, directly or indirectly regulate HSC activation by paracrine mechanisms, via secreting cytokines or chemokines. Currently, Mφ-derived extracellular vesicles (EVs) are broadly involved in cell communication with adjacent cell populations. However, whether Mφ-derived EVs could target neighboring HSCs to regulate their activation during schistosome infection remains largely unknown. Schistosome egg antigen (SEA) is considered to be the main pathogenic complex mixture involved in liver pathology. Here, we demonstrated that SEA induced Mφ to produce abundant extracellular vesicles, which directly activated HSCs by activating their autocrine TGF-β1 signaling. Mechanistically, EVs derived from SEA-stimulated Mφ contained increased miR-33, which were transferred into HSCs and subsequently upregulated autocrine TGF-β1 in HSCs through targeting and downregulating SOCS3 expression, thereby promoting HSC activation. Finally, we validated that EVs derived from SEA-stimulated Mφ utilized enclosed miR-33 to promote HSC activation and liver fibrosis in S. japonicum-infected mice. Overall, our study indicates that Mφ-derived EVs play important roles in the paracrine regulation of HSCs during the progression of hepatic schistosomiasis, representing a potential target for the prevention of liver fibrosis in hepatic schistosomiasis.